COMPARATIVE LEGAL ANALYSIS OF NON-CASH MONEY, ELECTRONIC MONEY AND THE DIGITAL RUBLE - KARPENKO A.A. (Legal Bulletin)
The relevance. Cashless settlements and e-money have responded to the need to speed up and simplify exchange transactions in a globalized and digitized economy. Electronic payment systems and bank transfers have made it possible to optimize the settlement process and make it more transparent and efficient. In turn, the emergence of cryptocurrencies and blockchain technologies has opened a new chapter in the history of money, offering decentralized forms of settlement independent of traditional financial institutions. The popularity of remote means of payment requires proper legal regulation, which, at the current stage, faces a number of difficulties and contradictions. The main goal. To identify the main characteristics of non-cash money, electronic money and digital ruble The problems under consideration. The author analyzes the economic and legal definition of “money” and determines whether this category covers non-cash monetary funds. The study examines the conflict between the concepts of digital currency and digital ruble, which acts as a “new form of national currency”, as well as the technological inaccuracy of attributing the digital ruble to non-cash money. The methods used. The article uses interdisciplinary approaches to illuminate the legal essence of “money” and its individual forms, which became available to economic entities with the development of digitalization. The formal-legal method was used in analyzing the legislative material.